An Invasive Mussel (Arcuatula senhousia, Benson 1842) Interacts with Resident Biota in Controlling Benthic Ecosystem Functioning - Guillaume Bernard; Laura Kauppi; Nicolas Lavesque; Aurélie Ciutat; Antoine Grémare; Cécile Massé; Olivier Maire (Journal of Marine Science and Engineering, 2020)
The invasive mussel Arcuatula senhousia has successfully colonized shallow soft sediments worldwide. This filter feeding mussel modifies sedimentary habitats while forming dense populations and efficiently contributes to nutrient cycling. In the present study, the density of A. senhousia was manipulated in intact sediment cores taken within an intertidal Zostera noltei seagrass meadow in Arcachon Bay (French Atlantic coast), where the species currently occurs at levels corresponding to an early invasion stage. It aimed at testing the effects of a future invasion on (1) bioturbation (bioirrigation and sediment mixing) as well as on (2) total benthic solute fluxes across the sediment–water interface. Results showed that increasing densities of A. senhousia clearly enhanced phosphate and ammonium effluxes, but conversely did not significantly affect community bioturbation rates, highlighting the ability of A. senhousia to control nutrient cycling through strong excretion rates with potential important consequences for nutrient cycling and benthic–pelagic coupling at a broader scale. However, it appears that the variability in the different measured solute fluxes were underpinned by different interactions between the manipulated density of A. senhousia and several faunal and/or environmental drivers, therefore underlining the complexity of anticipating the effects of an invasion process on ecosystem functioning within a realistic context.